RELIABILITY ANALYSIS OF THE MECHANICAL PROPERTIES OF 30MnB4 HIGH STRENGTH STEEL BOLTS UNDER STATIC LOADING CONDITIONS - Bozca, Mehmet; Kinit, Umut (YILDIZ TECHNICAL UNIV, 2020)
The objective of this study is to investigate the mechanical properties of high-strength steel bolts under static loading conditions based on reliability analysis. High-strength steel bolts samples were manufactured by sequential cutting, cold forming, heading and heat treating. All sample bolts were fully threaded hexagon cap M12 bolts, and the material was 30MnB4. During the heat treatment, quenching and tempering processes were applied to the high-strength steel bolts. A standard tensile test was performed on the samples. Stress-strain curves were obtained for the steel bolt samples after different heat treatments. The mechanical properties of the steel bolts, such as yield strength and tensile strength, were determined for the different heat treatments. Reliability analyses of the mechanical properties of the steel bolts under static loading conditions were conducted. The mean values, standard deviations and standard variables of yield strength and tensile strength were calculated. It was concluded that the reliability levels of yield strength and tensile strength (R>99%) satisfied the required yield strength values R-P0,R-2 and tensile strength values R-m given in the literature. Furthermore, having high reliability levels production is an advantage for manufacturer both in local and international markets.
Keywords: Reliability analysis; heat treatment; mechanical properties; bolt; Engineering